Quantitative determination of lamotrigi1ne in bulk and dosage form by UV Spectrophotometry - Navdeep Saini, Koyal Saini (Journal of Applied Pharmaceutical Science)
A new simple, rapid and precise spectroscopic method in UV region was developed for the quantitative determination of lamotrigine in bulk and in dosage form. In 0.1 M NaOH,Lamotrigine shows maximum absorbance at 307 nm. In proposed method Lamotrigine follows linearity in the concentration range 5-50 mcg/ml.The correlation coefficient for lamotrigine was found to be 0.99. The method was validated for Linearity, Precision and Accuracy.
Keywords: Lamotrigine, UV, Spectroscopic Method.